Implementing the concussion awareness training tool for high performance athletes - Babul, S.; Taylor, T.; Turcotte, K.; Bruin, S.; Karmali, K.; Wetherell, A.; Black, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Education is an essential component of sport-concussion protocols to improve management and avoid negative consequences associated with participants continuing to play through concussion symptoms. Tailored messaging is an effective way to help change the beliefs of those involved in concussion management. Partnering within government and provincial and national stakeholders, the Concussion Awareness Training Tool (https://cattonline.com/) was developed, which contain a series of evidence-based online educational modules and resources for various audiences including sport, health care, violence, and workplace related concussions. In 2019, partnering with U SPORTS (Canadian university sports-governing body), a new concussion education module with tailored messaging specific to high performance athletes (CATT-A) was created. The aim of this study was to evaluate the implementation of CATT-A among U SPORTS universities in Canada.